Estudio de factibilidad para la creación de una empresa de crianza, faenamiento y comercialización de pollo en la parroquia de Tambillo. - Bohórquez Tumbaico, Jefferson José (2020)
The present project for the creation of a chicken breeding, slaughtering and commercialization company in Tambillo parish, was carried out with the general objective of determining the feasibility of the business, subjecting it to a series of evaluations which are the methodology applied in the research. A market study was carried out in which several determining factors were found. It can be highlighted that in Canton Mejia there is a demand that is not completely met for chicken meat and that the consumption of the product in recent years has suffered a large percentage increase in per capita consumption. For the creation of the company, an initial investment of $ 248,934.77 is needed, which will be divided into the acquisition of fixed and deferred assets in addition to the working capital that will be needed to begin production operations. Once the technical study was conducted, it was determined that in order for the poultry plant to function normally, it is necessary to respect the regulations issued by AGROCALIDAD, comply with quality standards and the fiscal aspects established in the country. The shareholders' meeting will be composed of 2 partners who will be responsible for making decisions and 11 workers, thus generating alternatives that contribute to the development of our country. Having applied the financial evaluation through methods and procedures to be used to determine the feasibility and profitability of the implementation of the project of enterprise, we obtained a positive NPV of $ 78,178.86 that as an indicator presents a profitable business, also obtained an IRR of 26% which doubles the percentage of the TMAR, each of these data obtained determined that the business idea generates profitability and therefore is feasible.